Jogos de empresas como uma ferramenta lúdica no desenvolvimento de habilidades empresariais: um estudo de caso na engenharia de produção da UFAL - Muniz, Lucas Maciel (2016)
This paper aims create an environment that make possible the approach of business and industrial with reality that students of graduate course of production engeeniering will have after graduating process, With these concepts studied on subjects involving management area, this research has found in the business games the way to turn closer theory with practice. In doing so, we are using the Imagem e Ação game as a methodology tool in a engaging workshop wich has addressed business and entrepreneurship concepts, providing us from the behavior analysis and individual/collective interviews, results that prove the efficacy of business games on teaching-learning process and consequently it is concluded that the business games can be a methodology really useful in the simulating of reality, building business sceneries, stimulating the enterprising and managerial creativity of the teams, according to possible situations to be faced daily in companies that act in a competitive atmosphere and in a globalised world.